Geriatrics Literature 2017 Year in Review. Issue 9 (12th September 2018) - Willham, Kaitlin; Covinsky, Kenneth; Widera, Eric
Abstract : We present 11 of the most effective articles from 2017 in geriatric medicine. Studies address topics including self‐driven advance care planning, unnecessary emergency department transfers from assisted living, effect of transcatheter aortic valve implantation on cognition, a modified Hospital Elder Life Program to reduce delirium after surgery, patient experience and provider understanding of nursing home placement, patient perspectives on recommendations to stop cancer screening, management of subclinical hypothyroidism, reduction of inappropriate medications in nursing homes, effect of lorazepam on end‐of‐life agitated delirium, and benefits of a novel exercise program on walking.